PERANCANGAN PESAWAT UAV KAMIKAZE GARUDA WISANGGENI - Anisa Nurpitriani, Gifani; Putra An'nur, Alif (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
Developments in aviation technology have expanded the use of Unmanned Aerial Vehicles (UAVs), particularly for operations requiring rapid response and long-range capabilities. Fixed-wing UAVs are a preferred choice due to their superior flight stability, energy efficiency, and longer endurance compared to multirotor types. One specific variant, the kamikaze UAV or loitering munition, requires efficient aerodynamic design, high structural integrity, and guaranteed operational reliability. This study aims to design the "Garuda Wisanggeni" fixed-wing kamikaze UAV at the conceptual design stage. The methodology includes establishing Design Requirements and Objectives (DR&O), aircraft configuration, weight distribution and center of gravity (CG) analysis, aerodynamic characteristics, flight performance, stability analysis, and determining flight envelopes through V?n diagrams. Furthermore, design modeling was conducted using CAD software to achieve a comprehensive visualization, while ensuring compliance with aviation regulations based on ICAO standards and the Ministry of Transportation of the Republic of Indonesia's regulations.